Characteristics of patients with lung cancer in clinical practice and their potential eligibility for clinical trials evaluating tyrosine kinase inhibitors or immune checkpoint inhibitors. (June 2022) - van Veelen, Ard; Abtahi, Shahab; Souverein, Patrick; Driessen, Johanna H.M.; Klungel, Olaf H.; Dingemans, Anne-Marie C.; van Geel, Robin; de Vries, Frank; Croes, Sander
Abstract: Introduction: In- and exclusion criteria of randomized clinical trials (RCTs) aim to include a homogeneous study-population. This study compared characteristics of lung cancer patients from phase III RCTs evaluating tyrosine kinase inhibitors (TKIs) or immune checkpoint inhibitors (ICIs) with characteristics of lung cancer patients in a real world setting in the United Kingdom. Methods: A retrospective study was conducted using the Clinical Practice Research Datalink GOLD. Patients (N = 9239) with a first ever lung cancer registration between 2014 and 2018 were identified. Eligibility for inclusion was assessed for twelve RCTs (evaluating TKIs or ICIs). Reasons for potential exclusion and the number of unmet criteria were assessed for each RCT independently. OS was assessed using Kaplan-Meier and Cox proportional hazards analyses. Results: The proportion of potentially eligible patients was 74.3% and 51.9% for TKI and ICI RCTs, respectively. History of another malignancy, renal insufficiency or concomitant drug-use were main reasons for exclusion. OS was considerably longer for potentially eligible patients. Hazards ratios varied from 1.17 (95% confidence interval, 1.11–1.24) to 1.35 (1.20–1.42) across the RCTs. Conclusion: This study showed that a considerable proportion of lung cancer patients in a real-world setting would have been ineligible for participation in phase III RCTs and that potentially ineligible patients experienced a shorter OS. Highlights: A large proportion of lung cancer patients were ineligible for trial participation. Eligibility was higher for studies evaluating TKIs compared to ICIs. Most patients would be excluded based on 1 or 2 unmet criteria. Main reasons for exclusion were another malignancy or concomitant drug-use. Eligible patients had considerably longer OS compared with ineligible patients.